Hindsight and popular astronomy - Whiting, Alan B. (World Scientific, 2011)
There are many books that endeavor to bridge the gap between scientists and laymen, yet too many overemphasize the presentation of scientific findings as hard facts and end up alienating readers from the critical thinking processes involved in science. Whiting attempts to break away from the norm in this revolutionary review of popular astronomy books written from 1833 to 1944. He examines these important works by acknowledged authorities in the field to see how they have stood the test of time. Where the luminaries have failed, he looks for clues that the layman reader could have used to rais.